PENGEMBANGAN BUKU CERITA MATEMATIKA INTERAKTIF SEBAGAI MEDIA PEMBELAJARAN DI KELAS III SEKOLAH DASAR - Laila Intan Fadila; Harjati, Purwiro; Alfarisi, Muhamad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mathematics learning in elementary schools continues to face various challenges, particularly because many mathematical concepts are abstract and difficult for students to understand. Observations conducted in Grade III Bilal bin Rabbah at Muhammadiyah Sang Pencerah Elementary School, Metro City, revealed that students perceive mathematics as a difficult and uninteresting subject and that existing learning media are insufficient to help them understand mathematical concepts concretely. This study aims to develop an interactive mathematics storybook as a learning medium for the topic of length measurement and to determine the validity and practicality of the developed product. The study employed a Research and Development (R&D) approach using the ADDIE development model, which consists of Analysis, Design, Development, Implementation, and Evaluation. The product was created using Canva as an illustrated storybook equipped with interactive activities, simple challenges, and QR codes linking to instructional videos. The results showed that the developed interactive mathematics storybook achieved an average validation score of 83% (highly valid), consisting of 81% from material experts, 84% from media experts, and 86% from language experts. Furthermore, the practicality test yielded scores of 90% from teachers and 96% from students (highly practical). These findings indicate that the product meets criteria for content validity, media design, language quality, and ease of use, making it suitable and practical for elementary mathematics instruction. Keywords: Interactive Mathematics Storybook, Learning Media, Elementary School Mathematics, ADDIE Model